Molecular docking of 5-phenyl-5,6-dihydrotetrazolo-[1,5-c]quinazolines to ribosomal 50s protein L2P (2QEX - Antypenko, O. M.; Antypenko, L.; Kalnysh, D.; Kovalenko, S. I.; Антипенко, Олексій Миколайович; Коваленко, Сергій Іванович (My University, 2022)
Given the presence of antimicrobial activity for various tetrazole derivatives and its condensed analogues, it was proposed to analyze 13 novel 5-phenyl-5,6-dihydrotetrazolo[1,5-c]quinazolines for molecular docking to ribosomal 50S protein L2P (2QEX) in comparison with Tedizolid, tetrazole-oxazolidinone antibiotic. Hence, 4-(5-methyl-5,6-dihydrotetrazolo[1,5-c]-quinazolin-5-yl)benzoic acid 12 proved to be the most probable in terms of antimicrobial activity in vitro as a result of in silico molecular docking to antimicrobial 2QEX target.
Antypenko O. M. - https://orcid.org/0000-0002-8048-445X; Kovalenko S. I. - https://orcid.org/0000-0001-8017-9108.
Keywords: 5-phenyl-5,6-dihydrotetrazolo[1,5-c]quinazolines; molecular docking; ribosomal 50S protein L2P (2QEX)